“And Again, the Skald Will Add Someone Else’s Song”: “Marine”, “Scottish”, “May” and Other Ballad Stylizations by Georgy Ivanov - Elena Yu. Kulikova (Гуманитарный вектор, 2020)
The thematic justification involves demand for detecting and identifying patterns of transformation and modification of ballads by poets of the Silver Age. The twentieth century loved poetry experiments, a game with form, and there are a variety of genres: sonnets, rondos, gazella, pantoons, ballads in the works of symbolists and especially those of the Acmeists. Acmeist ballads reveal a part of the early twentieth century poetic world and contain both the traditional elements of the genre and the features of modernism. The works by Georgy Ivanov, the so-called “youngest acmeist”, who was a member of the Petrograd “Workshop of poets”, presents a variety of lyrical genres. The purpose of our study is to consider the ballads and ballad stylization of G. Ivanov. The purpose of the work determines its methodological basis, which includes the historical and literary, phenomenological, typological and comparative approaches. The stylization which is inherent in all of Ivanov’s ballads (“Song of the Pirate Ola”, “May Ballad”, “Scottish Ballad”, “Ballad about the Publisher”) and his ballad poems, allows to see the genre in a new aspect. The poet observes ballad rules – a tragic plot, romantic “vagueness” of narration, ballad motifs (ominous raven, night stories, turning into the past, etc.). However, these rules are distorted and stylized. Traditional ballad plots are so intensified that forcing the features creates a comic or ironic effect, the combination of motives turns out to be multilayer. G. Ivanov creates a parody in some cases and in some cases, a stylized ballad. The game and the love of stylization which characterize G. Ivanov throughout his creative life open up a new genre that he practically created by himself